#TITLE_ALTERNATIVE# - JANUARI WAHYUDI (NIM 22308010); Pembimbing: Dr. Wawan Gunawan A. Kadir, dan Dr. Hendra Grandis, EKO
In this magister thesis, I demonstrate the possibility of inversion 4D gravity data (surface and borehole) using genetic algorithm. Genetic Algorithm combines the biology genetic concept and optimization function that maximize the fitness with artificial evolution process.